Working Capital Management and Bank Performance in Nigeria: Comparative Study of Zenith Bank Nigeria PLC - Sandra Adaeze AGUZUE; Benjamin EHIKIOYA; Franklin Famous ASEMOTA; Michael Abidemi ADEWOLU; Bukola Bolanle AWOGBENJA (Communications of International Proceedings, 2022)
The paper investigated deposit money banks’ working capital management and how it has impacted bank performance in Nigeria using Zenith Bank PLC as study case. The concepts of working capital management and bank performance were examined. Bank performance was measured with return on asset. The pecking order theory was explained and linked with the study while some empirical literatures were reviewed. Variables like working capital and asset returns of Zenith Bank PLC was used for the study. The study also used the comparative analysis technique by analyzing the financial statement of Zenith Bank PLC from 2010 till 2020. Findings from the analysis revealed a direct relationship between working capital and asset returns as for each year from 2010 till 2020, as whenever the value of working capital increases or reduces the value of asset returns follow suit. The study therefore recommended that the management of Nigerian banks should give adequate attention to working capital management as it can help boost performance.
Keywords: Working Capital; Working Capital Management; Bank Performance; Asset Return; Observation